Technology innovations: the cause or solution to human wildlife conflict? - Mustafa, Maizatun (2018)
The development of science and technology has had enormous benefits for humanity. However, the relationship between technologies and environmental sustainability is complex. While its innovative use in expanding the bounds of conservation strategies is recognised, increased damage to the natural world has also been associated with the application of technology. For a country such as Malaysia which continues to face challenges in managing human wildlife conflict (HWC), technology has increasingly becoming an important tool within the law in managing such conflict. On the other hand, while technological tools can be applied to enhance wildlife protection, it can also be misused or exploited. This include the usage of technology to commit various wildlife crime such as illegal trading or poaching. This paper presents an overview of issues pertaining to HWC in Malaysia and highlights current legal approach in managing the issues. The paper also discusses the application of technology to support enforcement of the law and identifies challenges faced in combatting wildlife crime involving advanced technology. The paper concludes that development of innovative technologies can possibly bring about conflicting consequences. However policymaker as well as authorised agencies should identify actual and potential contribution of technologies and should fully utilize them to support wildlife conservation and to fight wildlife crime. On this basis, the utilization of technology which is changing nature conservation in increasingly profound ways could therefore increase the ability to manage HWC and enhance human-wildlife coexistence.